The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00338-009-0534-4
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface enrichment of zooplankton over a shallow back reef: implications for coral reef food webs

Abstract: Zooplankton were 3-8 times more abundant during the day near the surface than elsewhere in the water column over a 1-2.4 m deep back reef in Moorea, French Polynesia. Zooplankton were also significantly more abundant near the surface at night although gradients were most pronounced under moonlight. Zooplankton in a unidirectional current became concentrated near the surface within 2 m of departing a well-mixed trough immediately behind the reef crest, indicating that upward swimming behavior, rather than near-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 46 publications
1
44
1
Order By: Relevance
“…data), we hypothesize that the approximate coincidence of wave-forced, cross-reef transport and acroporid reproduction produces elevated recruitment along the southwest shore. Thus, the back reef of Moorea is affected by seasonally variable cross-reef transport of offshore water (Hench et al 2008), which transports zooplankters over the reef crest and into the lagoon (Alldredge & King 2009). This flow would also transport coral larvae when coral reproduction is coincident with powerful waves, and influence thermal heterogeneity within the back reef as cross-reef transport varies in intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…data), we hypothesize that the approximate coincidence of wave-forced, cross-reef transport and acroporid reproduction produces elevated recruitment along the southwest shore. Thus, the back reef of Moorea is affected by seasonally variable cross-reef transport of offshore water (Hench et al 2008), which transports zooplankters over the reef crest and into the lagoon (Alldredge & King 2009). This flow would also transport coral larvae when coral reproduction is coincident with powerful waves, and influence thermal heterogeneity within the back reef as cross-reef transport varies in intensity.…”
Section: Discussionmentioning
confidence: 99%
“…This flow would also transport coral larvae when coral reproduction is coincident with powerful waves, and influence thermal heterogeneity within the back reef as cross-reef transport varies in intensity. Although we did not measure the transport of coral larvae across the reef crest and, in fact, coral larvae were not found in one recent study that assessed the flux of zooplankton across the reef crest in Moorea (Alldredge & King 2009), the presence of juvenile colonies of outer reef corals (e.g. Pocillopora eydouxi and Astreopora myriophthalma) behind the reef crest in some locations suggests that the delicate coral larvae can pass over the reef crest, settle, and grow into new recruits (P. J. Edmunds pers.…”
Section: Discussionmentioning
confidence: 99%
“…The description of three-domain spatial patterns within marine microbial communities in the context of the oceanic waters surrounding the coral reef ecosystem of Moorea is a key step in understanding the diversity and stability of planktonic microbial populations between coastal and open water oligotrophic ecosystems. The barrier reef system surrounding Moorea's Paopao Bay and adjacent lagoons has been the subject of several long-term biological (Adjeroud and Salvat, 1996;Adjeroud, 2000;Adjeroud et al, 2002;Penin et al, 2007;Alldredge and King, 2009), biogeochemical and oceanographic (Schrimm et al, 2004;Hench et al, 2008) research studies, though this study and a parallel report (Nelson et al, 2011) are the first to describe this ecosystem's microbial populations, this report being the first one to do so across all three domains of microbial life. A companion study recently demonstrated strong spatial patterns in dissolved organic carbon, bacterioplankton densities and bacterial community structure between and among the inshore and offshore habitats (Nelson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, competition between photosynthesis and calcification for limited HCO 3 -could impact F v /F m in a pattern dependent on flow and temperature (as in massive Porites; Edmunds & Lenihan 2010), although evidence from Stylophora pistillata suggests this might only occur at very low concentrations of HCO 3 -1 (Furla et al 2000). Flow can impact corals in more ways than mass transfer alone, and on the reef the patterns implicating flow that were detected in a microcosm study would likely be modified through the roles of water motion in modulating the fluxes of zooplanktivorous food (Alldredge & King 2009) and particle capture rates (Sebens et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These coral structures, referred to as 'bommies', can reach > 3 m diameter and > 2 m height, and are often colonized by smaller branching corals, other invertebrates, and algae. In a recent demographic survey of branching corals in the back reef of Moorea, we found that growth and survival of juvenile Pocillopora verrucosa (colonies < 40 mm diameter) was higher on bommies compared with the adjacent seafloor, because bommies provide access to increased water flow (Lenihan et al 2008), a greater flux of zooplankton (Alldredge & King 2009), and reduced rates of sedimentation (Lenihan et al 2008). We have found only minor differences in temperature and light between the seafloor and the tops of bommies in this location (Lenihan et al 2008), and differences in these factors are probably not responsible for the observed differences in coral performance on these 2 substrate types.…”
Section: Methodsmentioning
confidence: 99%